Aromatic Polyamines Covalent Triazine Polymer as Sorbent for CO2 Adsorption - Lee, S.-P. (Institute of Physics Publishing, 2017)
A novel aromatic polyamine covalent triazine-based polymer, CPDA was obtained by the polymerization of amino group (1,4-phenylenediamine) and cyanuric chloride. CPDA was characterized with Fourier Transform Infra-red spectroscopy (FTIR) and the thermal behaviour was studied with thermal gravimetric analysis (TGA) and derivative thermal analysis (DTA). A comparison study for CO2 adsorption capacity on covalent organic polymer 1 (COP-1) and CPDA was performed. By introducing the aromatic ring into the nitrogen fertile triazine based system, the thermal stability of the network is enhanced. Polymer structure containing secondary amine functionality was observed in this study. Besides, the suggested chemical pathway is another approach to synthesis of covalent organic materials using economic monomers and absence of expensive catalyst. © Published under licence by IOP Publishing Ltd.